2010
DOI: 10.1007/s13206-010-4311-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased poly(dimethylsiloxane) stiffness improves viability and morphology of mouse fibroblast cells

Abstract: We monitored the viability and morphology of mouse fibroblast cells cultured on PDMS substrates with different degrees of polymer stiffness. The stiffness was controlled by varying the ratio between base and crosslinker agent during mixing. Although the standard PDMS mixing ratio is 10 : 1 (base to crosslinker; Young's modulus, E= =580 kPa), we found that a PDMS substrate with a high stiffness (mixing ratio of 5 : 1, E= =1,000 kPa) was more favorable as a substrate for fibroblast cell growth. It is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 33 publications
7
67
0
Order By: Relevance
“…For subcutaneous implants test, tissues of 1, 2, 4, 8 weeks after implantation were examined. As expected from several reports [19,20], any inflammation was not observed in all tissue samples. For the detail inspection, all samples were H&E-stained and observed through the microscopy.…”
Section: Resultssupporting
confidence: 90%
“…For subcutaneous implants test, tissues of 1, 2, 4, 8 weeks after implantation were examined. As expected from several reports [19,20], any inflammation was not observed in all tissue samples. For the detail inspection, all samples were H&E-stained and observed through the microscopy.…”
Section: Resultssupporting
confidence: 90%
“…In particular, Engler et al's report [7] that stiffer substrate (25e34 kPa) can induce osteogenic differentiation of mesenchymal stem cells (MSCs) while softer one (0.1e17 kPa) can enhance myogenic and neurogenic differentiation, has sparked numerous investigators to consider the effect of stiffness on cell behaviors. A variety of materials, including polyacryl amide (PAA) [3], polyethylene glycol (PEG) [13], PAA/PEG interpenetrating polymer network (IPN) [14], polydimethyl siloxane (PDMS) [15], hyaluronic acid (HA) [16], and collagen [17], have been adopted to strengthen this concept and optimize the substrate's stiffness for controlling cell behaviors. During the initial stage, many of these investigations used separate substrates with different, randomly selected degrees of stiffness, which provided limited information in stiffness ranges, neither critical values to sophisticatedly regulate cell behaviors by stiffness, nor any mimicking of tissue microenvironments with heterogeneous (gradient) stiffness (e.g., tendonto-bone tissue, osteochondral tissue, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Other individual physical properties such as roughness and hydrophobicity could be also changed through PDMS formulation and affect the behaviours of muscular and neural cells [17] as well as fibroblasts [21], which suggested that PDMS may render a versatile platform to study the combinatorial effects of substratum properties on stem cell behaviour.…”
Section: Introductionmentioning
confidence: 99%